(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
In this article, we adhere to a broad understanding of the term hyperhyponymy and focus on the analysis of the «extreme» components of hyperhyponymic groups - those that have the widest, most abstract philosophical meaning (words) as hyperonyms, on the one hand, and on the other hand, differential features of hyponyms, grouped as wide as possible. Special primary zone of categorization, which has a specific primary zone of categorization, last grouped prototypes of categories are repeated and most often found in different associative fields. How a word moves up and down the vertical axis of categorization depends on how much it contrasts with other members of the category, that is, acquires a more or less specific meaning. At the same time, such a shift may occur within one level of categories, and may be accompanied by a transition of language to another level.